Localization of RNA and translation in the mammalian oocyte and embryo - Jansova, Denisa (PLoS One, 2018)
The tight correlation between mRNA distribution and subsequent protein localization and function indicate a major role for mRNA localization within the cell. RNA localization, followed by local translation, presents a mechanism for spatial and temporal gene expression regulation utilized by various cell types. However, little is known about mRNA localization and translation in the mammalian oocyte and early embryo. Importantly, fully-grown oocyte becomes transcriptionally inactive and only utilizes transcripts previously synthesized and stored during earlier development. We discovered an abundant RNA population in the oocyte and early embryo nucleus together with RNA binding proteins. We also characterized specific ribosomal proteins, which contribute to translation in the oocyte and embryo. By applying selected markers to mouse and human oocytes, we found that there might be a similar mechanism of RNA metabolism in both species. In conclusion, we visualized the localization of RNAs and translation machinery in the oocyte, that could shed light on this terra incognita of these unique cell types in mouse and human.